2018
DOI: 10.1016/j.molcel.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

PELI1 Selectively Targets Kinase-Active RIP3 for Ubiquitylation-Dependent Proteasomal Degradation

Abstract: Receptor-interacting protein kinase-3 (RIP3 or RIPK3) is a central protein in necroptosis, but posttranslational processes that regulate RIP3 activity and stability remain poorly understood. Here, we identify pellino E3 ubiquitin protein ligase 1 (PELI1) as an E3 ligase that targets RIP3 for proteasome-dependent degradation. Phosphorylation of RIP3 on T182 leads to interaction with the forkhead-associated (FHA) domain of PELI1 and PELI1-mediated K48-linked polyubiquitylation of RIP3 on K363. This same phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 56 publications
1
87
2
1
Order By: Relevance
“…MLKL is a key effector of necroptosis and upon activation by phosphorylated RIP1, RIP3 will recruit and phosphorylate MLKL to execute necroptosis 30 . During this process, MLKL forms an oligomer and translocates to the plasma membrane to cause membrane rupture.…”
Section: Discussionmentioning
confidence: 99%
“…MLKL is a key effector of necroptosis and upon activation by phosphorylated RIP1, RIP3 will recruit and phosphorylate MLKL to execute necroptosis 30 . During this process, MLKL forms an oligomer and translocates to the plasma membrane to cause membrane rupture.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that Peli1 was an E3 ubiquitin ligase mediating protein activation or stability through adding the poly-ubiquitin chains to the substrates [ 26 , 37 39 ]. The increased C/EBPβ protein levels in Peli1 -knockdown microglial cells promoted us to investigate whether Peli1 directly regulated the ubiquitination of this transcription factor.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, several checkpoint regulators may be necessary to block the uninhibited progress of necroptosis. Recently, several proteins modulating necroptosis have been reported [17][18][19][20][21][22][23][24][25][26][27]. These regulatory proteins are limited in the pre-necrosome complex step, which consists of the process before the formation of the RIPK1/RIPK3 complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to RIPK1 modification, RIPK3 posttranslational modifications are crucial events in necroptosis. CHIP and Pellino 1 ubiquitinate and degrade RIPK3 protein levels in an ubiquitin-mediated lysosome- and proteasome-dependent manner, suppressing necroptosis [ 24 , 25 ]. A20 removes RIPK3 ubiquitination, which restricts necrosome complex formation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%